The Competitiveness of Indonesian Sugar Export in The South East Asia Region - Abdullah, Muhammad Irfani; Wijayanti, Irene Kartika Eka; Kusnaman, Djeimy (JURNAL AGRIBISAINS, 2023)
Sugar industry has an important role in the Indonesian economy because of its ability to absorp a lot of manpower.  AFTA (ASEAN Free Trade Area) provides transaction convenience both export and import between the member of ASEAN.  This study aims to analyze the competitiveness of Indonesian sugar export inside ASEAN area and to estimate the trend of Indonesian sugar export.  The competitiveness analysis uses RCA (Revealed Comparative Advantage) method while trend estimation uses Trend analysis.  The RCA analysis result shows that Indonesia has low competitiveness but shows progress in last 3 years.  While RCA analysis of Thailand and Myanmar shows declining trend.  The declining trend of Thailand’s RCA is caused by the development of sugar cane based ethanol industry.  While the declining trend of Myanmar’s RCA is caused by the decrease of sugarcane area and only temporary.  The trend analysis result shows that Indonesian sugar export is increasing.  The main export destination country for Indonesian sugar product is Vietnam.  Vietnam also shows increasing trend in sugar import.  So it will become an opportunity for Indonesia to increase its export value.